The Fits and Starts of Indian Rice Domestication: How the Movement of Rice Across Northwest India Impacted Domestication Pathways and Agricultural Stories - Bates, Jennifer (Frontiers in Ecology and Evolution, 2022)
Rice is currently the staple food for over 3.5 billion people and is arguably the most important crop exploited by humans. It is estimated that by 2025, the amount of rice needed to sustain current demand will have to increase by 25%. Understanding how we came to this point, where a single crop dominates the lives of almost half of the Earth’s population has major significance for our future, even more so given the climatic instability we face today, as rice is a cereal that is dependent on water to an extreme degree. In this paper the nature of early rice agriculture in South Asia is explored, looking at how this critical crop may have begun to be exploited, cultivated and then brought under agricultural regimes during the long span between c.6500 and 1500BC. There is now clear evidence for early Holocene cultivation of rice in the Middle Gangetic plains of northern India, but there is still considerable debate about the timing of when this cultivation began and whether it involved the domestication of rice. By 3200BC however rice agriculture was present outside the Ganges in the Indus Civilization. The Indus data that shows an accelerated domestication pathway once rice hits these new environments and agricultural systems, and this plays a part in the later hybridizations narratives when Chinese paddy rice arrives. Understanding how this move from its place of origin to a new environment may have played a part in the domestication pathways of South Asia rice prior to the arrival of Chinese rice c.1500BC are important to the overall rice story, as they play into modern concerns relating to biodiversity and different ways of growing and watering rice.